Chinese Motion-Directional Construction: A Conceptual and Cognitive Analysis - Fong Ronald (Sciendo, 2017)
This article proposes an analysis of the Motion-Directional Construction in Chinese in the Conceptual-Cognitive approach as outlined by Jackendoff and Langacker. This article first argues that the Motion-Directional Construction consists of conceptual subordination, expressing different mental spaces. Then, it examines the syntactic and semantic behaviors of the construction arguing that it is more like a constructional idiom. In particular, we discuss the case of pa ‘climb’ and generalize further that the motion verbs in Chinese typically express manners of movement. Within the Conceptual Semantics, we argue that a level of grammatical relation may not be necessary; it is the argument and conceptual structures that we need in the cognitive structure. Finally, we present the data and suggest the typological relevance of the Motion-Directional Construction.